Development of a Molecular Marker Linked to the A4 Locus and the Structure of HD Genes in Pleurotus eryngii. Issue 2 (3rd April 2019) - Lee, Song Hee; Ali, Asjad; Ha, Byeongsuk; Kim, Min-Keun; Kong, Won-Sik; Ryu, Jae-San
Abstract: Allelic differences in A and B mating-type loci are a prerequisite for the progression of mating in the genus Pleurotus eryngii ; thus, the crossing is hampered by this biological barrier in inbreeding. Molecular markers linked to mating types of P. eryngii KNR2312 were investigated with randomly amplified polymorphic DNA to enhance crossing efficiency. An A4 -linked sequence was identified and used to find the adjacent genomic region with the entire motif of the A locus from a contig sequenced by PacBio. The sequence-characterized amplified region marker 7-2299 distinguished A4 mating-type monokaryons from KNR2312 and other strains. A BLAST search of flanked sequences revealed that the A4 locus had a general feature consisting of the putative HD1 and HD2 genes. Both putative HD transcription factors contain a homeodomain sequence and a nuclear localization sequence; however, valid dimerization motifs were found only in the HD1 protein. The ACAAT motif, which was reported to have relevance to sex determination, was found in the intergenic region. The SCAR marker could be applicable in the classification of mating types in the P. eryngii breeding program, and the A4 locus could be the basis for a multi-allele detection marker.